Konsep Diri Remaja pada Masa Pubertas dan Implikasinya terhadap Layanan Bimbingan dan Konseling - Juliana Juliana; Indra Ibrahim; Afrizal Sano (Indonesian Institute for Counseling, Education and Therapy (IICET), 2014)
For students who are in puberty, they should have a self-concept in the face of changes experienced during puberty. Where they should have the knowledge, hope, and an assessment of the rapid body changes that occur at that time. But the facts on the ground, from observations and interviews that there are students who do not have a good self-concept in the face of puberty. This study classified the type of descriptive quantitative research. Research subjects were 79 students in the class VII puberty in SMP 13 Sijunjung. The research instrument is the questionnaire. Research findings reveal: in general students have a good self-concept in the face of puberty.